Action Program and Socialization of Plastic Waste Hazards for Health and Environment in Tanjung Kramat, Gorontalo - Intan Manyoe; Siti Suhartini S. Napu; Supriadi Supriadi; Taufik Hidayansya; Hisanari Sugawara (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
The Tanjung Kramat area is one of the areas on the southern coast of Gorontalo which is polluted by plastic waste. Activities are needed to increase public knowledge. The purpose of community service is to socialize the dangers of plastic waste to health and the environment and to carry out an action program to clean up the coastal and marine environment. Methods are identification and survey, socialization, and action program. The results show that through socialization and action programs there is a change in mindset and attitude patterns in the community. The community admitted that they only got knowledge about plastic waste during socialization activities. People expressed concern about the dangers of plastic waste. In the community action program, they no longer burn plastic waste. The community said that they could reduce the use of plastic waste, for example by replacing plastic shopping bags with shopping bags made of woven rattan. This community service is the first step for reducing the use of plastic waste in the Tanjung Kramat area.